Współczynnik Poissona Materiału Piezoelektrycznego i jego Pomiaru - Pajewski, W. (Engineering Transactions, 1974)
At the beginning, the definition of Poisson's ratio in anisotropic materials is given, and its measurement technique is described, based on the measurements of propagation velocities longitudinal and transversal waves, Resonance methods are discussed in detail, use being made of the vibration forms of slabs and bars suitably cut out from piezoelectric crystals.On the basis of experiments, several variants of vibration forms are indicated to be most appropriate for practical applications. The measurements made were used to determine the influence of boundary conditions on the value of Poisson's ratio in piezoelectric crystals.